High Level Production of Monoclonal Antibodies Using an Optimized Plant Expression System - Diamos, Andrew G.; Hunter, Joseph G. L.; Pardhe, Mary D.; Rosenthal, Sun H.; Sun, Haiyan; Foster, Bonnie C.; DiPalma, Michelle P.; Chen, Qiang; Mason, Hugh S. (Frontiers in Bioengineering and Biotechnology, 2020)
Biopharmaceuticals are a large and fast-growing sector of the total pharmaceutical market with antibody-based therapeutics accounting for over 100 billion USD in sales yearly. Mammalian cells are traditionally used for monoclonal antibody production, however plant-based expression systems have significant advantages. In this work, we showcase recent advances made in plant transient expression systems using optimized geminiviral vectors that can efficiently produce heteromultimeric proteins. Two, three, or four fluorescent proteins were coexpressed simultaneously, reaching high yields of 3-5 g/kg leaf fresh weight or ~50% total soluble protein. As a proof-of-concept for this system, various antibodies were produced using the optimized vectors with special focus given to the creation and production of a chimeric broadly neutralizing anti-flavivirus antibody. The variable regions of this murine antibody, 2A10G6, were codon optimized and fused to a human IgG1. Analysis of the chimeric antibody showed that it was efficiently expressed in plants at 1.5 grams of antibody/kilogram of leaf tissue, can be purified to near homogeneity by a simple one-step purification process, retains its ability to recognize the Zika virus envelope protein, and potently neutralizes Zika virus. Two other monoclonal antibodies were produced at similar levels (1.2-1.4 g/kg). This technology will be a versatile tool for the production of a wide spectrum of pharmaceutical multi-protein complexes in a fast, powerful, and cost-effective way.